Herbal Skincare: Formulation, Testing and Analysis of Moisturizer and Lip Balm - Beenakshi Thakur,; Dr. Puneet,; Gurinder Singh,; Harpreet Kaur, (International Journal of Scientific Research in Science and Technology, 2025)
The herb is a plant that is valued for its aromatic and therapeutic properties. The products used to enhance a one's look are known as herbal cosmetics. An herbal face moisturizer and lip balm are created and evaluated using plant-based ingredients that have skin-nourishing, moisturizing, and healing properties. Natural oils and waxes like beeswax, emulsifying wax, shea butter, and coconut oil and olive oil were combined with herbal extracts like calendula officinalis, Narcissus tazetta and citrus sinensis to create the face moisturizer and lip balm. The aim of this study is to create herbal moisturizer and lip balm with various herbal plants. Both formulations were evaluated for their physicochemical properties, stability, spread ability, skin friendliness, and moisturizing ability. This study demonstrates the development of a skin compatible formulations with suitable pH, texture and consistency. Stability test under various storage conditions indicates a good shelf life supporting the potential for practical applications. The natural compounds improved the hydration and preservation of the skin and lips without causing any negative side effects. This study also shows the possibility of herbal cosmetics as a safe, efficient, and ecologically friendly substitute for synthetic formulations.
Keywords: Herbal; cosmetics; skincare; lip balm; Calendula; Narcissus; Citrus; oils; beeswax; shea butter; eco-friendly; moisturizing